Using the electrochemical impedance spectroscopy to characterize carbon steel in biodiesel medium - Akita, A. H. [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Aoki, I. V.; Benedetti, Assis Vicente [UNESP] (The Electrochemical Society, 2012)
Electrochemical impedance spectroscopy measurements using two carbon steel electrodes in soybean biodiesel medium, produced by methylic route, were performed in an electrochemical cell that allows positioning the two electrodes face-to-face. To retain the biodiesel between the electrodes and prevent its leakage a porous membrane soaked in biodiesel was used. The amplitude of the AC potential and the area of the electrodes were varied. The linearity between disturbance and response signals was observed for tests when the amplitude of the AC potential was lower than 1500 mV (rms). The electrical resistance of biodiesel dominates the global response and carbon steel presents low corrosion, which is observed only at low frequency, and was confirmed by chemical tests performed in the membrane. In conclusion the electrical resistance of biodiesel can be estimated using electrochemical impedance spectroscopy with two electrodes set up. ©The Electrochemical Society.
Keywords: Carbon steel electrodes; Chemical tests; Electrical resistances; Electrochemical impedance spectroscopy measurements; Global response; Porous membranes; Response signal; Soybean biodiesels; Carbon steel; Corrosion; Electric resistance; Electrochemical impedance spectroscopy; Electrodes; Spectroscopy; Biodiesel